2018
DOI: 10.1590/1678-992x-2016-0337
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping Acacia mangium stimulates AMF colonization and soil phosphatase activity in Eucalyptus grandis

Abstract: Arbuscular mycorrhizal fungi (AMF) are very important to plant nutrition, mostly in terms of acquisition of P and micronutrients. While Acacia mangium is closely associated with AMF throughout the whole cycle, Eucalyptus grandis presents this symbiosis primarily at the seedling stage. The aim of this study was to evaluate the dynamics of AMF in these two tree species in both pure and mixed plantations during the first 20 months after planting. We evaluated the abundance, richness and diversity of AMF spores, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 46 publications
(64 reference statements)
2
33
0
4
Order By: Relevance
“…When mixed with eucalypt, acacia does change the soil microbial and bacterial communities, which are strongly correlated to N, C and P contents, revealing a more effective nutrient cycling, greater stimulation of microbial activity in litter and soil (Bini et al 2012(Bini et al , 2013Pereira et al 2017). Furthermore, arbuscular mycorrhizal fungi root colonization and the activity of acid and alkaline phosphatase increased in eucalypt intercropped with A. mangium with further improvement in P cycling P nutrition (Bini et al 2018).…”
Section: Discussionmentioning
confidence: 95%
“…When mixed with eucalypt, acacia does change the soil microbial and bacterial communities, which are strongly correlated to N, C and P contents, revealing a more effective nutrient cycling, greater stimulation of microbial activity in litter and soil (Bini et al 2012(Bini et al , 2013Pereira et al 2017). Furthermore, arbuscular mycorrhizal fungi root colonization and the activity of acid and alkaline phosphatase increased in eucalypt intercropped with A. mangium with further improvement in P cycling P nutrition (Bini et al 2018).…”
Section: Discussionmentioning
confidence: 95%
“…et al (2007);Bini et al (2017);Breuninger et al (2000);Caproni et al (2005);Carrenho et al (1998); Cavallazzi et al (2007); Fernandes et al (2016); Focchi et al (2004); Freitas et al (2014); Gomes and Trufem (1998); Lammel et al (2015); Leal et al (2016); Mello et al (2006); Moreira et al (2007); Moreira et al (2009); Moreira-Souza et al (2003); Pagano et al (2009); Pagano and Scotti (2008); Pereira et al (2014); Pontes et al (2017); Purin et al (2006); Santos et al (2013); Silva et al (2007); Silva et al (2014); Souza et al (2010); Souza et al (2016); Teixeira et al (2017); Teixeira-Rios et al (2018); Trindade et al (2006); Vilcatoma-Medina et al (2018); Zandavalli et al (2008).…”
mentioning
confidence: 98%
“…in intercropped cucumber rhizospheres. Similarly, Bini et al (2018) found that intercropping Acacia mangium stimulated arbuscular mycorrhizal fungi colonization in Eucalyptus grandis. Therefore, it was possible that the decreased cucumber Fusarium wilt severity was associated with the increased abundance of plant-beneficial microbes when intercropped with wheat.…”
Section: Discussionmentioning
confidence: 83%